COVID-19 outcomes in UK centre within highest health and wealth band: a prospective cohort study. Issue 11 (16th November 2020) - Ken-Dror, Gie; Wade, Charles; Sharma, Shyam; Law, Jessica; Russo, Cristina; Sharma, Aarti; Joy, Elizabeth; John, Joshua; Robin, Jonathan; John, Sarah; Mahana, Karim; Fluck, David; et al.
Abstract : Objectives: To describe the characteristics and outcomes of hospitalised patients with COVID-19 from UK in the highest decile of health and gross regional products per capita. Design: Prospective cohort study. Setting: Recruited all adult inpatients with laboratory-confirmed COVID-19 symptoms admitted to a single Surrey centre between March and April 2020. Extensive demographic details were documented. Outcome measure: COVID-19 status of alive/dead and intensive care unit (ICU) status of yes/no. Participants: Patients with COVID-19 from Surrey centre UK (n=429). Results: 429 adult inpatients (mean age 70±18 years; men 56.4%) were included in this study, of whom, 19.1% required admission to ICU and 31.9% died. Adverse outcomes were associated with age (OR with each decade of years: 1.78, 95% CI 1.53 to 2.11, p<0.001 for mortality); male gender (OR=1.08, 95% CI 0.72 to 1.63, p=0.72, present in 70.7%, of admissions to ICU versus 53% of other cases, p=0.004); cardiac disease (OR=3.43, 95% CI 2.10 to 5.63, p<0.001), diabetes mellitus (OR=2.37, 95% CI 1.09 to 5.17, p=0.028) and dementia (OR=5.06, 95% CI 2.79 to 9.44, p<0.001). There was no significant impact of ethnicity or body mass index on disease outcome. Conclusions: Despite reports of worse outcomes in deprived regions, we show similar complication and mortality rates due to COVID-19 in an affluent and high life expectancy region.